2013
DOI: 10.1117/12.2002513
|View full text |Cite
|
Sign up to set email alerts
|

Breast imaging with the SoftVue imaging system: first results

Abstract: For women with dense breast tissue, who are at much higher risk for developing breast cancer, the performance of mammography is at its worst. Consequently, many early cancers go undetected when they are the most treatable. Improved cancer detection for women with dense breasts would decrease the proportion of breast cancers diagnosed at later stages, which would significantly lower the mortality rate. The emergence of whole breast ultrasound provides good performance for women with dense breast tissue, and may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…The first device (Duric et al, 2007), an early prototype developed at the Karmanos Cancer Institute, has a ring array transducer with a 100 millimeter radius, 256 transducer elements, and a signal bandwidth centered at 1.5 MHz. The second device (Duric et al, 2013), a recent prototype developed by Delphinus Medical Technologies, Inc., has a transducer with a 110 millimeter radius, 2048 transducer elements, and a signal bandwidth centered at 2.75 MHz. For further details, see (Roy et al, 2013).…”
Section: Processing Of Experimental Datamentioning
confidence: 99%
“…The first device (Duric et al, 2007), an early prototype developed at the Karmanos Cancer Institute, has a ring array transducer with a 100 millimeter radius, 256 transducer elements, and a signal bandwidth centered at 1.5 MHz. The second device (Duric et al, 2013), a recent prototype developed by Delphinus Medical Technologies, Inc., has a transducer with a 110 millimeter radius, 2048 transducer elements, and a signal bandwidth centered at 2.75 MHz. For further details, see (Roy et al, 2013).…”
Section: Processing Of Experimental Datamentioning
confidence: 99%
“…3, [15][16][17][18][19][20][21] Of additional importance, UST provides the opportunity to conduct serial breast scans without the risk of ionizing radiation and to monitor changes in breast density over time. 18 Obtaining reliable estimates of density change is clinically relevant as a growing number of studies have demonstrated that changes in breast density are associated with response to some breast cancer treatments, such as tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach, used mostly in the field of breast imaging, is travel time tomography [10], [11]. Here, the speed of compression, or longitudinal, waves in tissue is measured based on the acoustic travel times between known location pairs.…”
Section: A General Backgroundmentioning
confidence: 99%